A Case of 17q21.31 Microduplication and 7q31.33 Microdeletion, Associated with Developmental Delay, Microcephaly, and Mild Dysmorphic Features - Adrian Mc Cormack; Juliet Taylor; Leah Te Weehi; Donald R. Love; Alice M. George (Case Reports in Genetics)
Concurrent cryptic microdeletion and microduplication syndromes have recently started to reveal themselves with the advent of microarray technology. Analysis has shown that low-copy repeats (LCRs) have allowed chromosome regions throughout the genome to become hotspots for nonallelic homologous recombination to take place. Here, we report a case of a 7.5-year-old girl who manifests microcephaly, developmental delay, and mild dysmorphic features. Microarray analysis identified a microduplication in chromosome 17q21.31, which encompasses the CRHR1, MAPT, and KANSL1 genes, as well as a microdeletion in chromosome 7q31.33 that is localised within the GRM8 gene. To our knowledge this is one of only a few cases of 17q21.31 microduplication. The clinical phenotype of patients with this microduplication is milder than of those carrying the reciprocal microdeletions, and suggests that the lower incidence of the former compared to the latter may be due to underascertainment.